Growth and Population Dynamics of Daphnia sp. on Different Fermented Nutrient Sources - Salsabil, Nurul Khalishah; Irfan, Irfan (Torani Journal of Fisheries and Marine Science, 2025)
Chicken manure is an organic material rich in nutrients and can be fermented using specific microbes to break down complex compounds into simpler forms. This fermentation process enhances the availability of nutrients that are more easily absorbed by aquatic organisms such as Daphnia sp., supporting their growth. This study aimed to evaluate the effect of different nutrient treatments on the growth and population dynamics of Daphnia sp. Three treatments were tested: unfermented chicken manure (A), chicken manure fermented with EM4 (B), and chicken manure fermented with yeast (C), each with four replications. A total of 100 g of chicken manure was fermented for three days before being used as a culture medium for Daphnia sp. The cultivation of Daphnia sp. lasted for 12 days in 2 liters of clean water per container, with an initial density of 50 individuals/L. Parameters observed included daily population growth and the timing of peak population. The results showed that treatment B (chicken manure fermented with EM4) produced a significantly higher population growth rate (P < 0.05). Meanwhile, the peak population of Daphnia sp. was observed simultaneously on day 9 across all treatments, based on descriptive observations. The population began increasing from the first day after stocking, peaked on day 9, and then declined until day 12 (end of the study). Water quality parameters during the study remained within a suitable range for Daphnia sp. growth. Therefore, fermentation of chicken manure using EM4 has the potential to improve the efficiency of Daphnia sp. population growth.